Immunometabolism features of metabolic deregulation and cancer - Wang, Xue; Ping, Feng‐Feng; Bakht, Sahar; Ling, Jingjing; Hassan, Waseem (Journal of cellular and molecular medicine, 2019)
Immunometabolism is a branch dealing at the interface of immune functionalities and metabolic regulations. Considered as a bidirectional trafficking, metabolic contents and their precursors bring a considerable change in immune cells signal transductions which as a result affect the metabolic organs and states as an implication. Lipid metabolic ingredients form a major chunk of daily diet and have a proven contribution in immune cells induction, which then undergo metabolic pathway shuffling inside their ownself. Lipid metabolic states activate relevant metabolic pathways inside immune cells that in turn prime appropriate responses to outside environment in various states including lipid metabolic disorders itself and cancers as an extension. Although data on Immunometabolism are still growing, but scientific community need to adjust and readjust according to recent data on given subject. This review attempts to provide current important data on Immunometabolism and consequently its metabolic ramifications. Incumbent data on various lipid metabolic deregulations like obesity, metabolic syndrome, obese asthma and atherosclerosis are analysed. Further, metabolic repercussions on cancers and its immune modalities are also analysed.